A Reflexive Gaze to the Urban Development of the Sudoeste del Besos Housing Estate - Guerra Mirón, Miguel (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2015)
The objective of this text is to lay out the evolution and current state of the Sudoeste del Besós housing estate in Barcelona. Built between 1960 and 1965 following a design by the architectural firm LIGS, it has undergone transformations throughout the years due to several urban interventions. This paper tries to update the debate about this kind of housing estates that appeared as a response to the lack of dwellings in the cities due to rural flight. The moment and circumstances in which these estates were designed and built has been taken into account, as well as the process of evolution and several renovations that have been made in this precise case. The necessary update of this kind of estates in the current city has been considered, and also the need to establish better connections with the nearest neighbourhoods and with the whole city. This text highlights a series of recent debates and reflections about the role and destiny that these estates have in the future of our cities.